Meningkatkan Hasil Belajar Matematika Dengan Metode Quipper School Pada Sd Negeri 4 Kaloran - Aisyah, Uud; Ermawati, Elisa; Hajron, Kun Hisnan (Prosiding University Research Colloquium, 2021)
The purpose of this study is to see how using the learning media Quipper School affectselementary school children 4 Kaloran's enthusiasm in learning mathematics. Thisstudy's findings were obtained by quantitative approaches, such as interviews withelementary school instructors, such as Ibu Juni Prihatin, S.Pd. Students from SD Negeri4 Kaloran, a total of 20 students, were the subjects of this study. Only students with amath score of 65-70 on the Mathematics test were chosen as part of the sample. Thisstudy used two test tests with an average score of 30.72 for the first test group of 20students, with the highest score of 40 and the lowest score of 20. The average score forthe second test group of 20 students was 48.56, with the highest value being 90 and thelowest being 40. The average value of the two classes' pretests is much below thespecified value of 7.5, which is the minimal completeness criterion. According to thecalculation data, there were 5 students who had a strong interest in learningmathematics, 9 students who had a sufficient interest in learning mathematics, and 6students who had no interest in learning mathematics before using themedia QuipperSchool. In addition, students in the class had an average interest in learning inmathematics classes of 74.3 percent. Using Quipper School means that the increase orsuccess that students achieve is increasing as a result of achieving better grades thanbefore the learning media was given Quipper School, indicating that this method iseffective in improving the learning scores of elementary school students in Mathematics.